2017
DOI: 10.1021/acs.jpcc.7b09187
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Considerable Metal Cation Concentrations from Lithium Intercalation Compounds in the Nano–Bio Interface Gap

Abstract: An experimental investigation of how electrostatics and ion dissolution impact the interaction between nanosheets of lithium intercalation compounds and supported lipid bilayers has revealed evidence for considerable metal cation concentrations in the nanosheets−bilayer (the "nano−bio interface") gap. Specifically, elevated concentrations of aqueous metal ions in the 1 mg/L concentration regime produce vibrational sum frequency generation signal intensity changes that are commensurate with the induction of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…The frequencies corresponding to the signal peaks in the C-H stretching region shown in Figure 1A are comparable to the ones we observe for supported lipid bilayers formed on fused silica substrates (see Supporting Information Figure S4) 25,27,30 The two broad features in the O-H stretching continuum located at ~3200 cm -1 and ~3400 cm -1 are associated with bandwidths (full width at half maximum) of about 200 cm -1 . The peak positions are within 50 cm -1 of what has been reported for water spectra obtained from symmetric bilayers prepared from negatively charged lipids on CaF 2 .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The frequencies corresponding to the signal peaks in the C-H stretching region shown in Figure 1A are comparable to the ones we observe for supported lipid bilayers formed on fused silica substrates (see Supporting Information Figure S4) 25,27,30 The two broad features in the O-H stretching continuum located at ~3200 cm -1 and ~3400 cm -1 are associated with bandwidths (full width at half maximum) of about 200 cm -1 . The peak positions are within 50 cm -1 of what has been reported for water spectra obtained from symmetric bilayers prepared from negatively charged lipids on CaF 2 .…”
Section: Resultssupporting
confidence: 82%
“…Figure 1A shows the ssppolarized SFG response from the pure DMPC bilayer without added salt. At this low ionic strength (~10 µM), we find clear spectral signatures from the C-H oscillators of the alkyl tails, 25,27,30 as well as broad contributions from the O-H stretches of the water molecules. The non-zero signals are due to the fact that the molecular environment above and below the bilayer is not fully symmetric, as would be expected for a suspended bilayer.…”
Section: Resultsmentioning
confidence: 88%
“…In the C-H stretching region, Figure 2A shows what we had reported earlier for the C−H stretching region, namely peaks at ~2880 cm -1 , ~2900 cm -1 , and ~2950 cm -1 characteristic of lipids in a well-formed bilayer. 8,9,34 The peak at ~2880 cm -1 is attributable to the symmetric CH 3 stretches of the lipid alkyl tails while the SFG intensity of the other two peaks is due to spectral interference from the water molecules, as demonstrated recently using D 2 O 34 and Page 7 spectral lineshape modeling. 26 Adding PAH to the bilayer leads to SFG intensity decreases, indicating a clear perturbation in the lipid structure with the addition of the polycations.…”
Section: Iid Pah-membrane Interaction Experiments Following Bilayermentioning
confidence: 74%
“…[3][4][5] Therefore, unanticipated changes to cell membranes can also alter their surrounding environment, ultimately disrupting important biological pathways. It has been reported that ions, polycations, and nanomaterials are prone to perturb supported lipid bilayers (SLBs), idealized model cell membranes, 3,6 and cause physical changes such as lipid asymmetry [7][8][9][10] and the formation of lipid coronas. [11][12][13][14] While informative, these results are specific to the SLBs and not their surrounding aqueous environment.…”
mentioning
confidence: 99%